STUDIUM PRZYPADKU W BADANIACH GLOTTODYDAKTYCZNYCH - Jaroszewska, Anna (Neofilolog, 2020)
The presented article is an attempt at providing a systematic outline of the basic information on the case study in the context of using in the language teaching studies. Surely, it is not discovering any new knowledge. It is rather a discussion of some obvious issues which especially young researchers frequently remain unconscious of. Simultaneously, it is aimed at provoking thinking on the topic, followed by popularising this highly interesting and valuable method as it enables to study any human activity, both the mental one and the one related to social relations, on many planes. Obviously, provided specific conditions are met.